Addressing Constraint Failures in Agent Interaction Protocol - Hassan, M.F.; Robertson, D.; Walton, C. (Springer Verlag, 2009)
The field of multi-agent systems shifts attention from one particular agent to a society of agents; hence the interactions between agents in the society become critical towards the achievement of their goals. We assume that the interactions are managed via an agent protocol which enables agents to coordinate their actions in order to handle the dependencies that exist between their activities. An agent’s failure to comply with the constraints attached within the protocol might cause a brittle protocol to fail. To address this problem, a constraint relaxation approach is applied using a distributed protocol language called the Lightweight Coordination Calculus (LCC). This paper describes the design and implementation of a constraint relaxation module to be integrated within the LCC framework. The working of this module is later illustrated using a scenario involving the ordering and configuration of a computer between the customer and vendor agents.